(untitled) (International Journal of Engineering and Computer Science, 2016)
— So many investigations are made on safety issues and data integrity auditing for sharing the dynamic data. Cloud computing provides secure remote data auditing for storage purpose. But it does not provide secure from collision of cloud storage server and revoked and revoked group customers during user revocation in practical cloud storage system. In This paper, we determine the collusion attack within the existing plan and supply a competent public integrity auditing plan with secure group user revocation according to vector commitment and verifier-local revocation group signature. We design a concrete plan in line with the plan explanation. Finally, the safety and experimental analysis expose that, in comparison using its relevant schemes our plan can also be safe and effective